An integrated scheduling method for AGV routing in automated container terminals. (December 2018) - Yang, Yongsheng; Zhong, Meisu; Dessouky, Yasser; Postolache, Octavian
Highlights: Based on the actual situation of loading and unloading operation mode in automated container terminals. The bi-level programming model of QCs, AGVs and ARMGs integrated scheduling. AGV path planning is the lower level, the integrated scheduling of QCs, AGVs, and ARMGs is the upper level. A bi-level General Algorithm based on the preventive congestion rule (CPR-BGA) to simulate the automated terminals. To achieve the optimized path and overcome the traffic bottleneck of AGVs. Abstract: The simultaneous scheduling of quay cranes (QCs), automated guided vehicles (AGVs), and yard cranes (YCs) in automated container terminals (ACTs) has been a critical problem. This paper proposes an integrated scheduling for handling equipment coordination and AGV routing. With the goal of minimising makespan, we set up a bi-level programming model. To solve the model, we investigate and compare the rolling horizon procedure (RHP) and Congestion Prevention Rule-based Bi-level Genetic Algorithm (CPR-BGA). It is shown that the CPR-BGA algorithm is highly effective for the integrated scheduling in ACTs. We conclude that the CPR-BGA is effective.